(untitled) (Global Journal of Management and Business Research, 2013)
This study is about the increasing trend of smoking in youth especially among university students which is increasing day by day. This cross sectional study was conducted from April 2013 to May 2013. A group of 200 students from university of Lahore took part in this study through a predesigned questionnaire which consists of 03 parts to meet the objectives of initial steps and reason behind smoking of youth. The results revealed that most of part of our youth is involved in use of smoking which is very dangerous for a country’s welfare. We conclude that smoking is an evil that can be eradicated through strict laws, government and parent’s supervision.